Novel Para-Probiotic – MOS Synbiotic Strategy to Improve Growth and Immune in Pacific Whiteleg Shrimp - Dian Eka Ramadhani; Erni Sulistiawati; Wida Lesmanawati; Ima Kusumanti; Cecilia Eny Indriastuti; Andri Iskandar; Wiyoto Wiyoto; Imam Tri Wahyudi; Rizky Fadilla Agustin Rangkuti (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research Paraprobiotic for intestinal health of shrimp. Growth performance and immune system increase during administration of paraprobiotics. Microencapsulation for making paraprobiotics. Pathogen inhibition by paraprobiotics. Abstract Vibriosis, caused by Vibrio spp., is a major threat in shrimp aquaculture, leading to high mortality and economic losses. Probiotics and prebiotics are promising preventive strategies to enhance host immunity and feed efficiency. This study aimed to determine the optimal dose of para-probiotic Pseudoalteromonas piscicida (1Ub) microcapsules and their combination with the prebiotic mannan-oligosaccharide (MOS) to improve growth performance and immune responses of Pacific whiteleg shrimp (Penaeus vannamei). The experiment was conducted at the College of Vocational Studies, IPB University, using mysis 2 (M2) larvae reared in 60 × 30 × 35 cm³ aquarium for two weeks until post-larvae stage 10 (PL10). Shrimp were fed synbiotic microcapsules (1% para-probiotic and 12 mg/L MOS) via bioencapsulated Artemia sp. Five groups were tested: K− (control, PBS immersion), K+ (challenged with Vibrio harveyi), A (0.5% synbiotic), B (1.0%), and C (2.0%). After 14 days, groups K+, A, B, and C were challenged with 10⁶ CFU/mL V. harveyi for seven days. Although differences were not statistically significant (P > 0.05), group A consistently showed better outcomes, including higher survival rate, final body length, total haemocyte count, respiratory burst, and phenoloxidase activity, along with lower Vibrio counts compared to K+. These trends indicate that synbiotic application, particularly at 0.5%, can enhance shrimp health and resilience. This study highlights synbiotics as a practical strategy to improve survival, growth, and disease resistance in larviculture.